Zimbabwe Public Administration Review : Initial Reflections on Public Sector Reform to Support the Economic and Social Recovery of Zimbabwe - World Bank (Washington, DC, 2017)
In early 2010, Zimbabwe's Minister of Public Service requested Bank support for a public administration review to provide analytical support and technical assistance to identify the key issues to restore the quality of public administration in Zimbabwe. This policy note presents an initial framing of recent public administration reform experiences and lessons learned in Zimbabwe and set the agenda for future client engagement with a view to present reform options. It has the following objectives: first, it intends to situate and analyze the current progress made and challenges facing the Zimbabwe public service in its wider and rapidly changing - economic and political context. Second, it aims at presenting the Bank's engagement in this area over the last three years and to synthesize what has been learned. Third, it identifies reform options given the current context and gives possible future entry-points. It mainly aims at providing an initial basis for client-engagement to reach a broad consensus on reform and the potential areas of Bank support. This note is structured into five chapters as follows: chapter one presents the introduction to this paper and the country context in Zimbabwe. Chapter two frames the role of the public administration in economic and social recovery and presents progress made and challenges in public administration reform. Chapter three discusses recent Bank support in key public sector management areas. Chapter four presents lessons learned by the Bank team throughout its recent engagement. Chapter five evaluates the reform space, options, priorities, and entry points.